The modern mathematics programme in some selected public elementary schools in its implementation - Talukdar, Kamaluddin Ahmad 1935- ([Quezon City s.n.], 1967)
The study determined the scope of the modern mathematics programme in selected elementary schools of Quezon City and some problems in its implementation.
Thesis (M.Ed.)--University of the Philippines
Keywords: Mathematics -- Study and teaching (Elementary).